2017
DOI: 10.5007/1980-0037.2017v19n1p62
|View full text |Cite
|
Sign up to set email alerts
|

High sedentary behavior and compromised physical capabilities in adult smokers despite the suitable level of physical activity in daily life

Abstract: DOI: http://dx.doi.org/10.5007/1980-0037.2017v19n1p62 Sedentary behavior may play an important role for health outcomes, regardless of the amount of physical activity in daily life (PADL).We aimed to evaluate and compare sedentary behavior as well as physical capabilities in physically active smokers and non-smokers. Twenty-eight adult smokers and 38 non-smokers free of lung disease were matched for age, sex, body mass index, body composition, cardiovascular risk and moderate-to-vigorous PADL. Participants und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Smokers tend to be sedentary, and high smoking levels are accompanied by increased sedentariness. 33,34 We found that when LSED increased to a certain level, the risk of smoking likewise increased significantly. This finding not only confirmed existing conclusions but also clarified the relationship between different levels of LSED and the risk of smoking.…”
Section: Discussionmentioning
confidence: 67%
“…Smokers tend to be sedentary, and high smoking levels are accompanied by increased sedentariness. 33,34 We found that when LSED increased to a certain level, the risk of smoking likewise increased significantly. This finding not only confirmed existing conclusions but also clarified the relationship between different levels of LSED and the risk of smoking.…”
Section: Discussionmentioning
confidence: 67%